Bibliometric and Visualized Analysis of China's Smart Grid Research 2008–2018 - Wang, Cheng; Lv, Tao; Deng, Xu (Frontiers in Research Metrics and Analytics, 2020)
Smart Grid (SG) has great advantages in renewable energy integration and has become the trend of modern power development currently; meanwhile China is the second most prolific country in SG. Hence the purpose of this study is to get access to the research status, development, and trends of SG in China based on the 3558 published papers obtained from the WOS core library and application of bibliometric method and visualization analysis software VOSviewer and alluvial diagrams. The results consequently demonstrate some valuable insights. Firstly, the volume of publications in China’s SG is on the rise, and the cooperation between countries and institutions is getting closer. Besides, the research hotspots are of obvious interdisciplinary characteristics. Taking into consideration of the impact of the information and communication field on SG, the major current research hotspots include wireless sensor network (WSN), internet of things (IoT), smart meter, big data, and security. Taking into consideration of the impact of SG on traditional power systems, the main hotspots cover demand response, micro-grid, distributed generation, and electric vehicle (EV). Furthermore, China’s SG research shows a trend from a single theme to a diversified development. The research themes during 2010-2018 have been deepened involving most studies of the traditional power system. These findings of this paper provide some enlightenment on China’s SG research, which can present scholars with an overview of the macro perspective, help to understand the latest development of the SG field in China and offer useful guidance for future research in this subject as well.